PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PADA DINAS PENDIDIKAN KOTA BANDUNG - Dedi Shihabudin Ahmad (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The long journey that the city of Bandung has gone through as the capital city of West Java Province has qualified experience requirements as the capital city of a province with a diverse and diverse population. The increase in population from day to day makes Bandung must be able to respond to various changes in a wise and dignified manner. One of them is that several organizations in the government area must be able to respond quickly to several changes that occur from one time to another. As happened with the Bandung city education office which continues to strive to realize good organizational quality along with the times to serve the community well. This study aims to understand the effect of motivation and work environment on employee performance at the education office in the city of Bandung. Using path analysis and quantitative methods and purposive sampling, a sample of 50 Bandung city education office employees was obtained. The findings from the results of the study that the motivation of an employee to win is not optimal, the working environment conditions are still not calm and the awarding of rewards from the leadership is still not optimal in the relationship between motivation, work environment and employee performance as a form of a new model in learning human resources.